Ivan Turgenev’s tale “Torrents of Spring” as a prose tragedy: Inner compulsion for mimetic competition as Sanin’s hamartia - Stephan Lipke (RUDN Journal of Studies in Literature and Journalism)
We study Ivan Turgenev’s tale “Torrents of Spring” as a prose tragedy. In the inner story, the unity of place, time, and action, so crucial to Aristotle’s concept of the tragedy, is observed. The analysis of the pieces of art mentioned in the story (Danneker’s “Ariadne”, Allori’s “Judith”) shows that there is also another element that is widespread in tragedies, predictions of the main character’s moral downfall and ‘enslavement’ to Maria Nikolaevna. For this reason, we can say that the tale is not only filled with tragic elements but can with full right be called a tragedy that contains the principal elements of this genre, with the exception of those referring directly to the scene or to declamation. Using René Girard’s theory, by studying the names of the other male characters, we can tell that the factor that moves the tragedy is Sanin’s hamartia, that is his inner compulsion to fulfill other people’s expectations, thus entering into mimetic competition with the other men. Sanin, who might have excelled Panteleimon, Émile, Klüber, and Dönhoff, finally creeps more than Polozov. However, the frame story allows for a potential catharsis, not only for the reader but also for Sanin himself.